(untitled) (Research, Society and Development, 2021)
The aim of this work was to evaluate and determine the morphological descriptors of accessions of ipecac. 66 accessions of ipecac preserved in vivo at Embrapa Amazônia Oriental, in Belém, PA, were evaluated, totaling 330 individuals, for five quantitative morphological characters. The data were submitted to multivariate analyzes, direct selection and selection with reanalysis were carried out grouped in two methods and based on the average Euclidean distance used in the formation of the clusters by the methods Unweighted Paired Group Method Using ArithmeticAverages -UPGMA for Tocher’s optimization and for analysis of main components. Of the five characters evaluated according to the two procedures used, none was redundant, so there were no discards. Based on the average Euclidean distance, they presented three shortest 0.09 distances; 0.17 and 0.20 between pairs of accessions and allowed to separate them into three divergent groups by the UPGMA method and by the Tocher method there was the formation of two divergent groups. Three characters presented the greatest contributions to the divergence, the leaf width, petiole length and plant height, with 80.04%. In view of this, all characters contributed to differentiate between accessions and accessions of C. Ipecacuanha, with leaf width, petiole length and plant height being the ones that most contributed to the divergence between accessions.